Basic Algebra Test P \mathfrak{P} a \mathfrak{a} r \mathfrak{r} t \mathfrak{t} 3 \mathfrak{3}

Algebra Level 4

Given that a , b , c , x , z , y R \displaystyle a,b,c,x,z,y \in \mathbb{R} and;

a 2 = b y + c z b 2 = c z + a x c 2 = a x + b y , \begin{aligned} a^2&=by+cz\\ b^2&=cz+ax\\ c^2&=ax+by, \end{aligned}

find the value of x a + x + y b + y + z c + z 3. \displaystyle \dfrac{x}{a+x} +\dfrac{y}{b+y} + \dfrac{z}{c+z} - 3.

Also try Basic Algebra Test Part 2 and Basic Algebra Test


The answer is -2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Satvik Golechha
Jan 5, 2015

a x + b y + c z a x + b y + c z = 1 \dfrac{ax+by+cz}{ax+by+cz}=1

a x a x + b y + c z + b y b y + c z + a x + c z c z + a x + b y = 1 \dfrac{ax}{ax+by+cz} +\dfrac{by}{by+cz+ax} +\dfrac{cz}{cz+ax+by}=1

a x a x + a 2 + b y b y + b 2 + c z c z + c 2 = 1 \dfrac{ax}{ax+a^2}+\dfrac{by}{by+b^2}+\dfrac{cz}{cz+c^2}=1

x a + x + y b + y + z c + z = 1 \dfrac{x}{a+x}+\dfrac{y}{b+y}+\dfrac{z}{c+z}=1

x a + x + y b + y + z c + z 3 = 2 \dfrac{x}{a+x}+\dfrac{y}{b+y}+\dfrac{z}{c+z}-3=\boxed{-2}

Pulkit Gupta
Sep 27, 2015

Let a = b = c =1. Then we may suppose x = y = z = 1/2. ( satisfies all the equations and conditions) Plug in values. You get the answer :)

Saurav Pal
Apr 7, 2015

a 2 = b y + c z b 2 = c z + a x c 2 = a x + b y \begin{aligned} a^2&=by+cz\\ b^2&=cz+ax\\ c^2&=ax+by \end{aligned} x = a 2 + b 2 + c 2 2 a x=\frac{-a^{2}+b^{2}+c^{2}}{2a} y = a 2 b 2 + c 2 2 b y=\frac{a^{2}-b^{2}+c^{2}}{2b} z = a 2 + b 2 c 2 2 c z=\frac{a^{2}+b^{2}-c^{2}}{2c} \therefore x a + x + y b + y + z c + z = 1 \displaystyle \dfrac{x}{a+x} +\dfrac{y}{b+y} + \dfrac{z}{c+z} = 1 1 3 = 2 1-3 = \boxed{\boxed{\boxed{-2}}}

Roy Tu
Jan 13, 2015

If you add the constraint that a = b = c a=b=c and x = y = z x=y=z (which we can do since the answer is constant, so long that a solution still exists) you'll notice that the three equations given boil down to one equation (which still has a solution):

a 2 = 2 a x a = 2 x a^2=2ax \\ a=2x

and the expression we are solving for looks like: x 2 x + x + x 2 x + x + x 2 x + x 3 = 1 3 = 2 \frac{x}{2x+x} + \frac{x}{2x+x} + \frac{x}{2x+x} - 3 \\ = 1 - 3 = \boxed{-2}

Mehul Chaturvedi
Jan 5, 2015

I got a = 2 x a=2x

And by symmetry, you can think like b = 2 y b=2y and c = 2 z c=2z

Pranjal Jain - 6 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...